2017
DOI: 10.1002/anie.201706228
|View full text |Cite
|
Sign up to set email alerts
|

Improved Biocompatibility of Black Phosphorus Nanosheets by Chemical Modification

Abstract: Black phosphorus nanosheets (BPs) show great potential for various applications including biomedicine, thus their potential side effects and corresponding improvement strategy deserve investigation. Here, in vitro and in vivo biological effects of BPs with and without titanium sulfonate ligand (TiL4) modification are investigated. Compared to bare BPs, BPs with TiL4 modification (TiL4@BPs) can efficiently escape from macrophages uptake, and reduce cytotoxicity and proinflammation. The corresponding mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
119
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(124 citation statements)
references
References 50 publications
(45 reference statements)
0
119
0
5
Order By: Relevance
“…Furthermore, the material has low cytotoxicity and hemolysis but was able to inhibit the growth of HeLa and HepG2 cells. Improved biocompatibility was observed for black phosphorus decorated with titanium sulfonate ligands, which can coordinate to black phosphorus surface …”
Section: Modificationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the material has low cytotoxicity and hemolysis but was able to inhibit the growth of HeLa and HepG2 cells. Improved biocompatibility was observed for black phosphorus decorated with titanium sulfonate ligands, which can coordinate to black phosphorus surface …”
Section: Modificationsmentioning
confidence: 99%
“…Furthermore,t he material has low cytotoxicity and hemolysis but was able to inhibit the growth of HeLa and HepG2 cells.I mproved biocompatibility was observed for black phosphorus decorated with titanium sulfonate ligands,which can coordinate to black phosphorus surface. [38] Interestingly,t he non-covalent interaction with alkali metals was reported. Ther eaction has to be well-controlled since alkali phosphide formation can take place,especially at elevated temperatures.T he interaction of few-layer black phosphorus with potassium was investigated in detail, and as trong electron-doping effect was observed on such ah eterostructure.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…P‐Ti coordination was taken to involve the lone‐pair electrons of phosphorus, thus avoiding the oxidation of BP by air and H 2 O. In addition, TiL 4 modification can also help BP to escape uptake by macrophages, and improve biocompatibility …”
Section: Modification Of 2d Nanomaterialsmentioning
confidence: 99%
“…[102,103] In addition to cytotoxicity,B Pn anostructures are able to induce immune perturbationd epending on the surface conditions. [104] The bioactivity of BP has recently been found to be selective. [107] By reducing the surface bioactivity of BP nanosheets through TiL 4 modification, Qu et al have attenuated the immune perturbation and inflammatoryr esponse in vitro and in vivo.…”
Section: Nanoscale Black Phosphorusmentioning
confidence: 99%
“…The bioactivity is originally regardeda sc ytotoxicity and depends on the fabrication process, [101] size, [102] applied dose, [103] and surfaceo xidation conditions. [104] Latiffe tal. have reported that BP nanostructures fabricated by vapor growth exhibit stronger cytotoxicity than those prepared by high-pressures ynthesis owing to theh igher degree of oxidation and stronger bioactivity in vitro.…”
Section: Nanoscale Black Phosphorusmentioning
confidence: 99%